Non-linear periodization for general fitness & athletes - Fleck, S. J. (Journal of Human Kinetics, 2011)
Periodization of resistance training or planned changes in training volume and intensity are used to maximize strength and fitness gains. Several types of periodized resistance training plans have been developed. The most common of these plans is linear also termed classic or strength/power periodization and nonlinear periodization. The biggest difference between these two types of training plans is with nonlinear periodization changes in training volume and intensity are made more frequently. The most common type of nonlinear periodization is daily nonlinear periodization where substantial changes in training intensity and volume are made from one training session to the next training session. Periodized resistance training does result in greater strength gains than non-periodized programs. While both linear and nonlinear periodization plans result in significant strength and fitness gains some research indicates greater strength gains with daily nonlinear periodization.